Bio-augmentation with dissimilatory nitrate reduction to ammonium (DNRA) driven sulfide-oxidizing bacteria enhances the durability of nitrate-mediated souring control. (1st July 2022) - Qi, Panqing; Sun, Dejun; Zhang, Gaixin; Li, Dongxia; Wu, Tao; Li, Yujiang
Highlights: DNRA-driven SOB enhances the durability of nitrate-mediated souring control. Heterotrophic DN reduces the durability of nitrate-mediated souring control. Autotrophic and heterotrophic nitrate reduction make SRB adaptable to nitrate. Bio-augmented souring control combined with bio-demulsification is achieved. Abstract: Biological souring (producing sulfide) is a global challenge facing anaerobic water bodies, especially the oil reservoir fluids. Nitrate injection has demonstrated great potential in souring control, and dissimilatory nitrate reduction to ammonium (DNRA) bacteria was proposed to play crucial roles in the process. How to durably control souring with nitrate amendment, however, remains undiscovered. Herein, Gordonia sp. TD-4, a DNRA-driven sulfide-oxidizing bacterium, was used to elucidate the effects of bio-augmentation with DNRA bacteria on the durability of nitrate-mediated souring control. The results revealed that nitrate amendment combined with bio-augmentation with TD-4 after souring could effectively control souring and enhance the durability of nitrate-mediated souring control, while nitrate amendment before souring failed to persistently control souring. Nitrate amendment before and after souring resulted in different evolution dynamics of nitrate-reducing bacteria. Denitrifying bacteria were enriched in reactors amended with nitrate before souring or in dissolved sulfide exhausted reactors amended with nitrate after souring. The heterotrophic denitrifying activity of denitrifying bacteria, however, decreased the durability of nitrate-mediated souring control. Comparative and functional genomics analysis identified potential niche adaptation mechanisms (autotrophic and heterotrophic nitrate/nitrite reduction, including DNRA and denitrification) of predominant SRB in nitrate-amended environments, which were responsible for the rapid resumption of sulfide accumulation after the depletion of nitrate and nitrite. Pulsed injection of nitrate combined with bio-augmentation with DNRA-driven sulfide-oxidizing bacteria was proposed as a potential method to enhance the durability of nitrate-mediated souring control. The findings were innovatively applied to simultaneous bio-demulsification and souring control of emulsified and sour produced water from the petroleum industry. Graphical abstract: Image, graphical abstract